THE INFLUENCE OF FINANCIAL PLANNING, FINANCIAL TECHNOLOGY, AND FINANCIAL INCLUSION ON IMPROVING MSME BUSINESS PERFORMANCE IN BANDAR LAMPUNG - Agustina Berliana; Habiburrahman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to determine how much influence financial planning, financial technology, and financial inclusion have on improving MSME business performance in Bandar Lampung. This study used quantitative methods with a sample of 100 respondents from MSMEs in Bandar Lampung City, the data in this study was processed using the help of SPSS Version 25.0 analysis. The results showed that financial planning had a significant positive effect on improving MSME business performance in Bandar Lampung, financial technology had a significant positive effect on improving MSME business performance in Bandar Lampung and financial inclusion did not have a significant positive effect on improving MSME business performance in Bandar Lampung.